Pupil dilation in the Simon task as a marker of conflict processing - Van Steenbergen, Henk; Band, Guido P. (Frontiers in Human Neuroscience, 2013)
Cognitive demands in response conflict paradigms trigger negative affect and avoidance behavior. However, not all response conflict studies show increases in physiological indices of emotional arousal, such as pupil diameter. In contrast to earlier null-results, this study shows for the first time that small (about 0.02 mm) conflict-related pupil dilation can be observed in a Simon task when stimuli do not introduce a light reflex. Results show that response-conflict in Simon trials induces both pupil dilation and reaction-time costs. Moreover, sequential analyses reveal that pupil dilation mirrors the conflict-adaptation pattern observed in reaction time. Although single-trial regression analyses indicated that pupil dilation is likely to reflect more than one process at the same time, in general our findings imply that pupil dilation can be used as an indirect marker of conflict processing.